Full-Color See-Through Three-Dimensional Display Method Based on Volume Holography - Taihui Wu; Jianshe Ma; Chengchen Wang; Haibei Wang; Ping Su (Sensors, 2021)
We propose a full-color see-through three-dimensional (3D) display method based on volume holography. This method is based on real object interference, avoiding the device limitation of spatial light modulator (SLM). The volume holography has a slim and compact structure, which realizes 3D display through one single layer of photopolymer. We analyzed the recording mechanism of volume holographic gratings, diffraction characteristics, and influencing factors of refractive index modulation through Kogelnik’s coupled-wave theory and the monomer diffusion model of photopolymer. We built a multiplexing full-color reflective volume holographic recording optical system and conducted simultaneous exposure experiment. Under the illumination of white light, full-color 3D image can be reconstructed. Experimental results show that the average diffraction efficiency is about 53%, and the grating fringe pitch is less than 0.3 μm. The reconstructed image of volume holography has high diffraction efficiency, high resolution, strong stereo perception, and large observing angle, which provides a technical reference for augmented reality.